Cooperation in small groups: The effect of group size - Daniele Nosenzo; Simone Quercia; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
Previous experiments have found a moderate, positive effect of group size on cooperation in voluntary contribution mechanism (VCM) games. This effect has been typically observed in experiments with groups of size 4 or more, and contrasts with results from n-person prisoner's dilemma and oligopoly experiments where group size has a negative effect on cooperation. In an attempt to reconcile these findings, we study VCM contributions in smaller groups. We conjectured that in groups of four or more players considerations about the social benefits of contributing, which increase with group size, may dominate any negative effect arising from the difficulties of cooperating in large groups. The negative effects of group size may instead be more evident in smaller groups. We test this conjecture in an experiment where we compare 2- 3- and 4-person VCM games. We find that contributions are highest in groups of two players and lowest in groups of three. This U-shaped contributions pattern suggests that offsetting positive and negative effects operate in VCM games.
Keywords: C72; H41; 330; voluntary contribution mechanism; cooperation; group size